2017
DOI: 10.1016/j.jcyt.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Cell density, dimethylsulfoxide concentration and needle gauge affect hydrogel-induced bone marrow mesenchymal stromal cell viability

Abstract: Mesenchymal stromal cells (MSCs) have shown potential therapeutic benefits for a range of medical disorders and maintain a focus of intense scientific investigation. Transplantation of MSCs into injured tissue can improve wound healing, tissue regeneration and functional recovery. However, implanted cells rapidly lose their viability or fail to integrate into host tissue. Hydrogel-seeded BM-MSCs offer improved viability in response to mechanical forces caused by syringe needles, cell density and dimethylsulfox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Technology development is needed to enhance the delivery, protection, and encapsulation of cells to increase the viability and local retention of cells when injected. Previous works have shown that hydrogels are promising alternatives to PBS for administration of cell therapies, as they enhance local retention and improve the viability of cells during injection when compared to injections performed in PBS . It has been proposed that hydrogel “plug flow,” a phenomena caused by the rheology of these materials, protects the cells from the shear and extensional forces during injection from a syringe and needle .…”
Section: Rheological Properties Of Hpmc:np and Alginate Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology development is needed to enhance the delivery, protection, and encapsulation of cells to increase the viability and local retention of cells when injected. Previous works have shown that hydrogels are promising alternatives to PBS for administration of cell therapies, as they enhance local retention and improve the viability of cells during injection when compared to injections performed in PBS . It has been proposed that hydrogel “plug flow,” a phenomena caused by the rheology of these materials, protects the cells from the shear and extensional forces during injection from a syringe and needle .…”
Section: Rheological Properties Of Hpmc:np and Alginate Materialsmentioning
confidence: 99%
“…Previous works have shown that hydrogels are promising alternatives to PBS for administration of cell therapies, as they enhance local retention and improve the viability of cells during injection when compared to injections performed in PBS. [10][11][12][13][14][15][16][17][18][19][20][21][22] It has been proposed that hydrogel "plug flow," a phenomena caused by the rheology of these materials, protects the cells from the shear and extensional forces during injection from a syringe and needle. [11] Hydrogels may also be used to provide an ECM mimic to enhance cell growth and differentiation.…”
mentioning
confidence: 99%
“…The optimum needle size for cell therapy varies depending on the application and injection site. While 25G and 27G needles are the most commonly used clinically, for instance in cardiovascular interventions, 38,39 larger diameter needles such as 22G and 23G are also used in many applications such as intra-articular delivery. 40,41 In addition, it is possible to further decrease the diameter of the microbeads.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The optimum needle size for cell therapy varies depending on the application and injection site. While 25G and 27G needles are the most commonly used clinically, for instance in cardiovascular interventions, , larger diameter needles such as 22G and 23G are also used in many applications such as intra-articular delivery. , In addition, it is possible to further decrease the diameter of the microbeads. In contrast to conventional methods, where changes in the nozzle diameter and process parameters would be required to achieve different microbead sizes, the emulsion process enables control of the average bead diameter by simply adjusting the stirring speed .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al proposed hydrogel-induced BM-MSCs under conditions of cell density (<2 × 10 7 cells/mL), DMSO concentration (<0.5%), and needle gauge (25G or 27G). The survival rate could be maintained above 82% (Chen et al, 2017). Osama et al proposed a different view: MSCs injected with a 30G needle showed significantly better viability when the hydrogel was in the pre-and post-gel state (Osama et al, 2018).…”
Section: Improving Mesenchymal Stem Cells Survivalmentioning
confidence: 99%